Analisis Kegiatan Alih Media Koleksi Ke Bentuk Digital Sebagai Upaya Pelestarian Di Perpustakaan Diplomasi Kementerian Luar Negeri - .A, Maharani Rizky; Samosir, Fransiska Timoria; Sa’diyah, Lailatus (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Transferring collection media to digital form is an activity that plays an important role in preserving the nation's cultural wealth by transferring its original form to digital media. The aim of this research is to understand the process of media transfer activities at the Diplomacy Library and identify the obstacles faced during the implementation of this activity. This research adopted a descriptive qualitative method involving observation, interviews and documentation. Data processing and analysis includes data reduction steps, data presentation, and drawing conclusions. The research results show that this media transfer activity is very important for collection preservation activities. Media transfer activities at the Diplomacy Library refer to the guidelines in the National Library of the Republic of Indonesia, because there are no special Standard Operating Procedures (SOP) created for the library. The main obstacle faced by the Diplomacy Library is the lack of human resources (HR) involved in managing media transfer activities. Therefore, to maintain the continuity of collection media transfer activities in diplomatic libraries, special attention is needed to human resource management in the future.Keywords: Media transfer, collection and preservation